Konstruksi Identitas Klub Sepakbola di Liga Indonesia: Studi Kasus Kepemilikan Klub Sepakbola Rans Nusantara FC Oleh Selebritis - Robby Rachman Nurdiantara; Kiki Esa Perdana (JIKA (Jurnal Ilmu Komunikasi Andalan), 2023)
Ownership of a sports club by celebrities is actually nothing new. In foreign countries, the business of owning a sports club like this is not only carried out by businessmen or large companies but also by celebrities. They consider that business in the sports sector is a promising form of investment. This study uses a qualitative approach, trying to understand and interpret the meaning of an interaction event between human behavior in situations according to the perspective of the researcher himself. In conclusion, the FC failed to construct identity. This failure can be said to be due to the unpreparedness of Rans Nusantara FC in facing the tough football competition. Keywords: identity construction, indonesian football, rans nusantara FC.